1994
DOI: 10.1111/j.1365-2133.1994.tb06873.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression in basal cell carcinoma: an immunohistochemical analysis

Abstract: Spontaneous regression of some cutaneous tumours is well recognized, and is thought to result from an immunological response to the tumour. Regression has previously been noted in basal cell carcinomas, but no studies defining the role of the immune response in the regression of this malignancy have been performed. We have examined 45 primary basal cell carcinomas (BCCs) (20 nodular, 25 superficial) and identified the cellular phenotypes and activation states of the cells infiltrating primary regressing and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
1
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 33 publications
8
105
1
7
Order By: Relevance
“…The spontaneous regression of these as well as of other tumors carries a great therapeutic potential, but the knowledge of the underlying mechanisms remains very limited. In BCC, tumor regression has been associated with cells of the immune system and certain cytokines (4,5), but the understanding of this phenomenon is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous regression of these as well as of other tumors carries a great therapeutic potential, but the knowledge of the underlying mechanisms remains very limited. In BCC, tumor regression has been associated with cells of the immune system and certain cytokines (4,5), but the understanding of this phenomenon is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Dellon et al (12) suggested that peritumoral lymphocytic infiltration may decrease the risk of recurrence influencing the regression of residual neoplastic cells. In addition, it has been hypothesized that T CD4 + lymphocytes, generally preponderant within the peritumoral inflammatory infiltrate, may induce regression through cytokine production (34). Nonetheless, in our observations, the inflammatory infiltrates were assessed with standard pathology haematoxylin-eosin staining analysis which, unlike immunohistochemical stainings, does not permit cell typization.…”
Section: Discussionmentioning
confidence: 99%
“…Such spontaneous regression is mediated by activated CD4+ T cells, and IFN-γ is elevated in actively regressing BCC (28). There is a significantly increased number of CD4+ T cells infiltrating regressing tumors, and the expression of IL-2 receptor, which is an early activation marker for T cells is also increased (29). Abundant CD8+ T cells and interferon signal transduction is associated with partial host antitumor response (2).…”
Section: Ifn-γmentioning
confidence: 99%